PEMANFAATAN KULIT BIJI KAKAO (THEOBROMA CACAO L) MENJADI PRODUK COOKIES COKLAT: (Utilization Of Cocono Seed Skin (Theobroma Cacao L) Become Chocolate Cookies Products) - Jumriah langkong; Meta Mahendradatta; Mulyati M Tahir; Nurlaila Abdullah; Marina Reski (Hasanuddin University Food Science and Technology Study Program, 2019)
Cocoa bean husk is one of the product of cocoa which is only utilized as animal feed and has low economic value. Economic value of cocoa bean husks can be enhanced by extracting the husk using methanol into powder and applied to a process product namely cookies. Cookies are types of biscuit which are made from soft dough, high in fat and relatively crisp. The purpose of this study was to determine the amount of powder that was added and its impact to the cookies product. The analysis was done for sensory test, moisture content, fat content and protein content. The result showed that water content ranged from 2.39% - 4.85%. Fat content ranged from 7.57% - 8.64%, and ash content ranged from 0.73% - 2.02%. In the organoleptic test, the color and odor which were preferred by the panelists was treatment A0 (control) whereas the taste and texture was treatment A1 (addition of 5% powder).